Upaya Penanggulangan Kasus Catcalling Di Lingkungan Perguruan Tinggi - Liza Deshaini; Darma, M. Tedi Setia; Ferdie Agusaputra; Nova Rendi; Apriliadi, Apriliadi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2025)
Catcalling in higher education is a problem that disrupts the comfort and safety of the academic community, especially for women. This study aims to analyze efforts to overcome catcalling through a normative approach by examining applicable regulations, campus policies, and the role of educational institutions in creating a safe environment. The research method used is normative legal research with the approach of legislation and literature study. The results show that catcalling prevention requires a combination of strict policies, education about sexual harassment, and active involvement of all campus elements in creating a culture of mutual respect. With a clear reporting mechanism and strict sanctions, it is hoped that catcalling cases can be minimized so as to create a safer and more inclusive campus environment.